2020
DOI: 10.1101/2020.03.17.995506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CYCA3;4 Is a Post-Prophase Target of the APC/CCCS52A2E3-Ligase Controlling Formative Cell Divisions in Arabidopsis

Abstract: 32The Anaphase Promoting Complex/Cyclosome (APC/C) controls unidirectional progression 33 through the cell cycle by marking key cell cycle proteins for proteasomal turnover. Its 34 activity is temporally regulated by the docking of different activating subunits, known in 35 plants as CDC20 and CCS52. Despite the importance of the APC/C during cell 36 proliferation, the number of identified targets in the plant cell cycle is limited. Here, we 37 used the growth and meristem phenotypes of Arabidopsis CCS52A2-def… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Those experimentally demonstrated to be phosphorylated are shown (closed red circles). Data are taken from the UNIPROT database (Hansen et al , ; Farkas et al , ; Rubin, ; Willems et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those experimentally demonstrated to be phosphorylated are shown (closed red circles). Data are taken from the UNIPROT database (Hansen et al , ; Farkas et al , ; Rubin, ; Willems et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that phosphorylated RBR1 can be detected in the nucleus of interphase cells in the form of granules (Abrahám et al , ), although the functional relevance of such foci remains to be determined. Proteomic studies have demonstrated RBR1 phosphorylation in vivo at residues T406, S652, and S911 (Reiland et al , ; Willems et al , ). The identification of other phosphorylated residues, as well as their functions, remains as a future challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation